Surgery combined with radio-chemotherapy for esophageal mucoepidermoid carcinoma: A case report. Issue 24 (June 2018) - Zheng, Chunhui; Chen, Xiaomei; Zhang, Fangbiao; Yan, Liping; Zhang, Xiangyan
Abstract: Rationale: Primary mucoepidermoid carcinoma (MEC) of the esophagus is a rare type of malignant neoplasm. Its morphology resembles that of MEC of the salivary glands. It is characterized by a diffuse mixture of squamous and mucus-secreting glandular carcinoma cells. Due to the low incidence of esophageal MEC, the biological behavior and treatment of this tumor have not been well studied. Patient concerns: In this case report, we describe a case of a 59-year-old man who presented with difficulty in swallowing. Iohexol swallowing revealed a malignant-appearing structure in the inferior-thoracic region. Diagnoses: Biopsy of the lesion under endoscopy demonstrated a mucoepidermoid carcinoma of the esophagus. Interventions: We performed esophagectomy, esophagogastrostomy through the esophageal bed and 2-field lymphadenectomy. Histopathological analysis of the tumor revealed histological characteristics typical of an esophageal MEC. Radio-chemotherapy was administered to this patient. Outcomes: Seventeen months after surgery, an esophageal computed tomography (CT) scan revealed that the wall of esophagus was evenly thickened. However, endoscopic assessment revealed no evidence of recurrence. Further CT scans at 19 and 31 months after surgery also showed a thickened esophageal wall, although endoscopic assessment at 31 months still revealed no esophageal stricture and no evidence of recurrence. The patient is alive with no dysphagia and no evidence of recurrence for over 39 months. Lessons: There is little evidence of effective treatment nor guidelines for treatment of esophageal MEC. Although the general prognosis of esophageal MEC is poor, comprehensive treatment of surgery and radio-chemotherapy appeared to be effective in this case. Radio-chemotherapy is a possible treatment option that was shown to have acceptable short-term effects.